The Development of Education of Public Health Nurses for Applying Genomics in Preventive Health Care - Laaksonen, Mari; Airikkala, Elisa; Halkoaho, Arja (Frontiers in Genetics, 2022)
Genetics and genomics have become one of the most important development areas in healthcare. For this reason, it is essential that nursing professionals take their role to offer their skills in implementing genomics in health promotion. The education of public health nurses is taking vital steps in training health promoters who are able to take genome-based knowledge into account in precision healthcare. Tampere University of Applied Sciences managed to integrate genomics into studies of public health nursing. This article describes the process of development and rises the importance of genomic education of public health nurses.